Supporting parenting during infant hospitalisation for CHD. (6th October 2020) - Gramszlo, Colette; Karpyn, Allison; Christofferson, Jennifer; McWhorter, Linda G.; Demianczyk, Abigail C.; Lihn, Stacey L.; Tanem, Jena; Zyblewski, Sinai; Boyle, Elizabeth Lucey; Kazak, Anne E.; Sood, Erica
Abstract: Objective: To characterise the parenting priorities of mothers and fathers of infants hospitalised with CHD and generate recommendations to support parenting during infant hospitalisation. Study design: Through online crowdsourcing, an innovative research methodology to create an online community to serve as a research sample, 79 parents of young children with CHD responded to questions about parenting during hospitalisation via private social networking site. Responses were analysed using qualitative research methods. Results: Three broad themes were identified: (1) establishing a bond with my baby, (2) asserting the parental role, and (3) coping with fear and uncertainty. Parents value provider support in restoring normalcy to the parenting experience during infant hospitalisation. Conclusions: Care teams can support parenting during infant hospitalisation by promoting parents' roles as primary caretakers and decision-makers and attending to the emotional impact of infant hospitalisation on the family.